Living across and through skins : transactional bodies, pragmatism, and feminism - Sullivan, Shannon, 1967- (Indiana University Press, 2001)
Explores the dynamic relationship between bodies and the world around them. What if we lived across and through our skins as much as we do within them? According to Shannon Sullivan, the notion of bodies in transaction with their social, political, cultural, and physical surroundings is not new. Early in the 20th century, John Dewey elaborated human existence as a set of patterns of behavior or actions shaped by the environment. Underscoring the continued relevance of his thought, Sullivan brings Dewey int.